Coping skills and burnout among medical officers in a Malaysian tertiary hospital / Nur Faizah Ali ... [et al.] - Ali, Nur Faizah; Raduan, Nor Jannah Nasution; Ismail, Zaliha; Razali, Salmi (Universiti Teknologi MARA Cawangan Selangor, 2020)
Burnout among doctors is hazardous, leading to stress which results in poor decision making and exposure to medical errors. This study aims to improve the knowledge gap of the issues of burnout and coping skills among medical officers. This study is a cross-sectional study involving 250 medical officers using universal sampling. Of the total 250 participants, 63 (25.2%) were burnout. The presence of burnout was significantly associated with dysfunctional coping skills (t=-4.96; p <0.001). Burnout is prevalent among medical officers. It is vital to take actions that can promote good mental health in the form of coping skills and resilience training.